A Case Study of an Analysis for E-Government Web Accessibility for the Disabled in Malaysia - Noraniza, Samat; Noorhuzaimi@Karimah, Mohd Noor; Rahmah, Mokhtar (2012)
The internet and World Wide Web has become important source of information. Graphical user interface, are designed for visual interaction through web for the user.Normal peoples can easily process the visual data and locate the information that is most relevant to them. However, this task can be time-consuming and difficult for people with disabilities. This paper will address the issue of designing accessibility government websites that substantially improves web browsing experience of people with disabilities. The study explores the web accessibility standards and guidelines, the web accessibility evaluation tools and then analyzing the government website in Malaysia. It investigates the issue of creating accessible website and the importance of implementing web accessible features to e-government websites. Then the evaluation of government websites using automated accessibility evaluation tools and manual testing according to the guidelines had been done to determine the adaption of W3C Web Content Accessibility Guidelines